Nudging in the Time of the Coronavirus : Evidence from an Experimental Tax Trial in Albania at the Onset of a Global Pandemic - Karver, Jonathan George; Shijaku, Hilda; Ungerer, Christoph T F (Washington, DC: World Bank, 2022)
This paper presents the results of a randomized controlled trial testing the effectiveness of taxpayer communications informed by behavioral science in inducing business payroll tax compliance at the onset of the COVID-19 pandemic. In March 2020, an experimental tax trial targeting 5,423 firms was implemented, coinciding with the national lockdown due to the global pandemic. The Albanian tax authority sent postal letters to employers and selected employees highlighting a suspicion that wages were under-declared to avoid personal income tax withholding. Employers and employees suspected of under-declaring were randomly assigned to receive a soft-tone letter (highlighting the social importance of contributing through taxes), a strong-tone letter (highlighting the penalties associated with under-declaring), or none (forming a control group against which the impact of receiving the letters could be estimated). For employers receiving soft-tone letters, the study finds large, statistically significant increases on subsequent payroll declarations (by as much as 10 percent relative to the control group), which gradually attenuate over the following six months. No statistically significant effects are found for letters sent to employees or strong-tone letters. The findings highlight (i) the importance of framing of communications as well as the importance of smart selection of letter recipients for taxpayer communication campaigns, (ii) which type of taxpayer communications were most effective in the context of the COVID-19 pandemic, and (iii) the role that randomized controlled trials and behavioral science can play in strengthening the effectiveness of government policy, particularly for public revenue mobilization.